Anti-Leishmania efecct of intralesional procaíne and dibucaíne in hamsters - Cazorla Perfetti, Dalmiro José; Yépez Hurtado, José Yancarlos; Añez Reverol, Néstor; Sánchez de Mirt, Auristela; Acosta Quintero, María Eugenia (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
The effect of intralesional treatment (IL) with Procaine and Dibucaine was compared with standard dosages of Glucantime® administered intramuscularly (IM) to attain clinical and parasitological cures in skin lesions in outbred male hamsters infected with Leishmania (Viannia) braziliensis. Results revealed that all drugs tested reduced significantly (P < 0.01) average lesion sizes in experimental animals when compared with those untreated. Local treatment with dibucaine was as clinically efficient as systemic Glucantime®, and more successful for clinical resolution than with procaine. Viable amastigotes were detected in nodules and/or scars in 100% of the evaluated hamsters 75-165 days after the end of the treatment ended, using smears, conventional histopathology, culture in NNN medium and the indirect immunoperoxidase method, suggesting that measurement of lesion sizes is not a valid criterion for evaluating the chemotherapeutic efficiency in experimental CL. The therapeutic clinic effectiveness of local anesthetics appeared to be associated with their half-life times as well as their lipid solubility. Preliminarily, these results appeared to support the inclusion of “cainic” local anesthetics as part of the alternative armamentarium in the treatment of animal and human cutaneous leishmaniasis (CL).